2012
DOI: 10.7205/milmed-d-11-00433
|View full text |Cite
|
Sign up to set email alerts
|

Medical Capacity Building Efforts in Northern Iraq 2009–2010

Abstract: The authors provide some back ground and general concepts for medical stability operations or medical civil military operations. Some novel programs were developed in northern Iraq, which have applicability to the greater military medical community. Train the trainer emergency medical technician and first aid course curriculums were developed and translated into Arabic and Kurdish and implemented by U.S. medics throughout northern Iraq. The Division also contracted with implementing partners to train first aid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 2 publications
0
4
0
Order By: Relevance
“…These studies found that conflict negatively affect the education and training of health workers leading to inadequate competencies, lower quality of education and limited professional development [ 20 - 23 ]. The training areas commonly tackled by the papers were emergency medicine, trauma care, first aid and midwifery [ 20 , 24 - 29 ]. The training were mainly provided by international aid organizations and through distant learning such as tele-education [ 20 , 23 , 28 - 31 ].…”
Section: Resultsmentioning
confidence: 99%
“…These studies found that conflict negatively affect the education and training of health workers leading to inadequate competencies, lower quality of education and limited professional development [ 20 - 23 ]. The training areas commonly tackled by the papers were emergency medicine, trauma care, first aid and midwifery [ 20 , 24 - 29 ]. The training were mainly provided by international aid organizations and through distant learning such as tele-education [ 20 , 23 , 28 - 31 ].…”
Section: Resultsmentioning
confidence: 99%
“…There was similar substantial programme during the Vietnam War as part of the ‘hearts and minds’ campaign ( Wilensky, 2004 ). Similar programmes were established in Iraq ( Michaud III and Maxwell, 2012: 676-680 ) and Afghanistan ( Bricknell and Cameron, 2011: S472-S476 ; Bricknell and Grigson, 2011: S468-S472 ). This is role now a recognised task for some military health services and is codified under the term military global health engagement covering both ‘military to military’ and ‘civilianmilitary’ activities ( Moten, et al, 2018: 14-17 ).…”
Section: Medical Contribution To Security and Stabilisationmentioning
confidence: 82%
“…This more expansive view of military strategy -that it involves more than the preparation and execution of combat operations -is reflected in the work of the highly influential David Kilcullen, an Australian infantryman seconded to the US State Department as Chief Strategist for counterterrorism. 88 As Michaud and Maxwell comment, it was 'hard to imagine stability operations not including a public health element', 89 and in 2010, 'medical stability operations' were formally identified by the DoD, whereby military assets would be used to maintain health system capacity as part of stabilisation operations. .…”
Section: Health Interventions For Strategic Effectmentioning
confidence: 99%
“…87 From 2005, a succession of DoD instructions and manuals saw stabilisation emerge as a key mission for the US military. 88 As Michaud and Maxwell comment, it was 'hard to imagine stability operations not including a public health element', 89 and in 2010, 'medical stability operations' were formally identified by the DoD, whereby military assets would be used to maintain health system capacity as part of stabilisation operations. 90 At the same time, ideas on how to use health to promote stability began to be developed.…”
Section: Health Interventions For Strategic Effectmentioning
confidence: 99%